2016
DOI: 10.1021/acs.jpcc.6b09374
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Signal Generation in Gold Nanospheres in Aqueous Solution: Signal Generation Enhancement and Particle Diameter Effects

Abstract: Gold nanoparticles can be used as an exogenous contrast agent for biomedical photoacoustic (PA) imaging. The generation of PA signals in monodispersed gold nanosphere suspensions (diameters 20–150 nm) from pulsed-laser excitation (5 ns pulse width, wavelength 532 nm) was investigated experimentally and compared to signals measured in solutions of a homogeneous molecular absorber. The PA signal amplitude was found to increase linearly with excitation fluence for the homogeneous absorber and the nanospheres up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 21 publications
3
48
1
1
Order By: Relevance
“…The gold nanospheres were found to sediment at the bottom of the tube, which differs from the experiments reported in Pang et al [13] on nanospheres suspended in water. To avoid any temporal changes in the local concentration of the gold nanospheres, imaging acquisitions were started at least 30 min after the preparation of the phantom to allow the particles to settle.…”
Section: Sedimentation Of the Gold Nanosphere Colloidcontrasting
confidence: 99%
See 2 more Smart Citations
“…The gold nanospheres were found to sediment at the bottom of the tube, which differs from the experiments reported in Pang et al [13] on nanospheres suspended in water. To avoid any temporal changes in the local concentration of the gold nanospheres, imaging acquisitions were started at least 30 min after the preparation of the phantom to allow the particles to settle.…”
Section: Sedimentation Of the Gold Nanosphere Colloidcontrasting
confidence: 99%
“…Additional non-linear functions were examined to fit the nonlinear PA signal in the gold nanospheres, including a third-order polynomial (R 2 3p = 0.98) and an exponential function (R 2 exp = 0.99). However, because neither of these alternatives provided a significantly better agreement with the data, and because the nonlinearity is expected to follow a quadratic function [13], the second-order polynomial was chosen for subsequent analysis. Figure 3 shows a schematic of the steps involved in the image analysis process of Method I as described in Section 2.4.…”
Section: Recovering the Spatial Distribution Of Gold Nanospheres Frommentioning
confidence: 99%
See 1 more Smart Citation
“…24 Gold nanoparticles can also exhibit changes in absorption after prolonged exposure, 9 with the added difficulty that their photoacoustic efficiency is not straightforward to model and characterize. 25,26 Inorganic absorbers such as Prussian blue and chloride salts such as CuCl 2 :2H 2 O and NiCl 2 :6H 2 O are highly photostable and have suitable spectra. 13 However, we have observed that the specific absorption spectra of the two chloride salts are affected both by their own concentrations and also by the presence of each other when dissolved in a mixture.…”
Section: Introductionmentioning
confidence: 99%
“…The laser energy density values used in this study are considered below the vaporization threshold based on previous measurements (400 mJ cm −2 for 250 nm gold nanoshells and 10 ns laser pulse, and dramatically increased vaporization threshold for smaller GNP) . To further confirm the nanoscale GNP heating, we measured the photoacoustic signal (Figure S1, Supporting Information) corresponding to thermoelastic expansion of the GNP and water, which is a result of the nanoscale heating. Furthermore, gold nanocrystals have vortexes and edges (Figure S5, Supporting Information) and lead to higher heat generation and altered temperature distribution of water around the GNP.…”
mentioning
confidence: 96%